NanoTRAIL‐Oncology: A Strategic Approach in Cancer Research and Therapy. Issue 11 (12th March 2018) - Shi, Yesi; Pang, Xin; Wang, Junqing; Liu, Gang
Abstract: TRAIL is a member of the tumor necrosis factor superfamily that can largely trigger apoptosis in a wide variety of cancer cells, but not in normal cells. However, insufficient exposure to cancer tissues or cells and drug resistance has severely impeded the clinical application of TRAIL. Recently, nanobiotechnology has brought about a revolution in advanced drug delivery for enhanced anticancer therapy using TRAIL. With the help of materials science, immunology, genetic engineering, and protein engineering, substantial progress is made by expressing fusion proteins with TRAIL, engineering TRAIL on biological membranes, and loading TRAIL into functional nanocarriers or conjugating it onto their surfaces. Thus, the nanoparticle‐based TRAIL (nanoTRAIL) opens up intriguing opportunities for efficient and safe bioapplications. In this review, the mechanisms of action and biological function of TRAIL, as well as the current status of TRAIL treatment, are comprehensively discussed. The application of functional nanotechnology combined with TRAIL in cancer therapy is also discussed. Abstract : Amounts of nanoparticles (e.g., liposomes, polymers, and other functional particles) have been widely investigated to enhance TRAIL antitumor efficacy. Nanoparticle‐based TRAIL (NanoTRAIL) has shown a great promise in cancer therapy due to its potential functions, such as enhanced permeability and retention effect, sustained release, active targeting, and synergistic effect combined with chemotherapeutics. The TRAIL‐based therapeutic strategies to overcome TRAIL resistance by utilizing nanoformulation and bioengineering are also introduced in this review.